2020
DOI: 10.1177/0960327120975122
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncRNA MIAT regulated by selenium and T-2 toxin increases NF-κB-p65 activation, promoting the progress of Kashin-Beck Disease

Abstract: LncRNA myocardial infarction associated transcript (MIAT) has been shown to be involved in osteoarthritis (OA), but its role in Kashin-Beck Disease (KBD) has rarely been reported. In this study, rats were administered with low selenium and/or T-2 toxin for 4 weeks to establish a KBD animal model. The serum selenium level, TNF-α and IL-1β contents, phosphorylated p65 (p-p65) and MIAT expression were increased in each intervention group. Next, we isolated the primary epiphyseal chondrocytes, and found that selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…13 The mechanism involved in mycotoxin toxicity includes lncRNA. 11,30 Several studies have found that exposure to aflatoxin B 1 (AFB 1 ) changes the expression of lncRNA and promotes the development of hepatotoxicity and cancer. 31−33 OTA induces the overexpression of lncRNA in renal cell carcinoma and is related to cell death pathways and metabolism.…”
Section: Long Noncoding Rna and Micrornamentioning
confidence: 99%
See 1 more Smart Citation
“…13 The mechanism involved in mycotoxin toxicity includes lncRNA. 11,30 Several studies have found that exposure to aflatoxin B 1 (AFB 1 ) changes the expression of lncRNA and promotes the development of hepatotoxicity and cancer. 31−33 OTA induces the overexpression of lncRNA in renal cell carcinoma and is related to cell death pathways and metabolism.…”
Section: Long Noncoding Rna and Micrornamentioning
confidence: 99%
“…Noncoding RNA is a key regulator of toxicological processes and a promising biomarker for the monitoring and prevention of mycotoxin contamination . The mechanism involved in mycotoxin toxicity includes lncRNA. , Several studies have found that exposure to aflatoxin B 1 (AFB 1 ) changes the expression of lncRNA and promotes the development of hepatotoxicity and cancer. OTA induces the overexpression of lncRNA in renal cell carcinoma and is related to cell death pathways and metabolism . The involvement of lncRNA in the regulation of mycotoxins is expected to become the focus of research because two lncRNAs (XLOC_302848 and XLOC_321638) are potential regulators of Fusarium head blight resistance .…”
Section: Long Noncoding Rna and Micrornamentioning
confidence: 99%
“… Reversing the effects of T-2 on chondrocyte injury. Shi et al. (2021) Rats Administered with T-2 (200 ng/g BW per day) for 4 weeks under the Se-deficient diet.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in leukocyte number and the decrease in bactericidal activity indicate that the T-2 can affect both non-specific cellular and humoral immunity in rainbow trout (Oncorhynchus mykiss) [18]. Ingestion of T-2-contaminated food not only can cause damage to tissues and organs, but also is closely related to degenerative joint diseases, such as Kashin-Beck disease (KBD) [19][20][21]. Propiconazole (PRO) is a triazole fungicide commonly used on corn, wheat, and vegetables worldwide [22].…”
Section: Introductionmentioning
confidence: 99%